2000
DOI: 10.1038/sj.bjp.0703333
|View full text |Cite
|
Sign up to set email alerts
|

Properties and pharmacological modification of ATP‐sensitive K+ channels in cat tracheal myocytes

Abstract: 1 The e ects of levcromakalim and nucleoside diphosphates (NDPs) on both membrane currents and unitary currents in cat trachea myocytes were investigated by use of patch-clamp techniques. 2 In conventional whole-cell con®guration, levcromakalim produced a concentration-dependent K + current which was suppressed by additional application of 5 mM glibenclamide at 770 mV. When 3 mM ATP was added in the pipette solution, the peak amplitude of the levcromakaliminduced current was much smaller than that in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The data recording system used was essentially the same as that described previously (Teramoto et al, 2000a). In short, generation of voltage pulses was performed using a L/M-EPC 8 patch-clamp ampli®er (HEKA Elektronik Corp., Lambrecht, Germany) in conjunction with a circuit board which has both an analogue to digital and a digital to analogue conversion function (ITC-16, Instrutech Corp., NY, U.S.A.), using a`Pulse' software package (HEKA Elektronik Corp., Lambrecht, Germany).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data recording system used was essentially the same as that described previously (Teramoto et al, 2000a). In short, generation of voltage pulses was performed using a L/M-EPC 8 patch-clamp ampli®er (HEKA Elektronik Corp., Lambrecht, Germany) in conjunction with a circuit board which has both an analogue to digital and a digital to analogue conversion function (ITC-16, Instrutech Corp., NY, U.S.A.), using a`Pulse' software package (HEKA Elektronik Corp., Lambrecht, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Patch-clamp experiments were performed at room temperature (21 ± 238C) as described previously (Teramoto et al, 2000a). Junction potentials between bath and pipette solutions were measured with a 3 M KCl reference electrode and were 52 mV, so that correction for these potentials was not made.…”
Section: Recording Proceduresmentioning
confidence: 99%
“…Patch‐clamp experiments were performed at room temperature (21–23°C) as described previously ( Teramoto et al ., 2000a , 2000b ). Junction potentials between bath and pipette solutions were measured with a 3 M KCl reference electrode and were <2 mV, so that correction for these potentials was not made.…”
Section: Methodsmentioning
confidence: 99%
“…The data recording system used was essentially the same as that described previously ( Teramoto et al ., 2000a , 2000b ). In short, generation of voltage pulses was performed using a L/M‐EPC 8 patch‐clamp amplifier (HEKA Elektronik Corp., Lambrecht, Germany) in conjunction with a circuit board which has both an analogue to digital and a digital to analogue conversion function (ITC‐16, Instrutech Corp., NY, U.S.A.), using a ‘Pulse’ software package (HEKA Elektronik Corp., Lambrecht, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A more recent study in tracheal smooth muscle has demonstrated ATP-sensitive currents activated by levcromakalim and corresponding single channels with a conductance of 40 pS. Uridine diphosphate reactivated these channels after rundown [192]. K ATP channel openers have potential for the treatment of airway hypercontractility [168].…”
Section: Airwaysmentioning
confidence: 98%